Marjorie Rice and the MAA tiling. Issue 2 (3rd July 2018) - Schattschneider, Doris
ABSTRACT: The tiling in the lobby of the headquarters building of the Mathematical Association of America (MAA) in Washington, DC, is unusual. Congruent pentagonal tiles fit together to fill the space, with no readily discernable pattern. Also unusual is the history of how the tiling came to be, and who discovered it. Not a mathematician, Marjorie Rice discovered this tiling while pursuing for years her self-assigned task of finding all types of convex pentagons that can tile the plane. GRAPHICAL ABSTRACT: